One Miracle After Another : The Pavel Goia Story - Budd, Greg (Review and Herald Publishing Association, 2009)
Pavel Goia knew when he was 5 years old that God had called him to speak for Him. Yet by the time Pavel reached his teens, having a good time with friends was far more important to him than his family’s religion. And communist Romania wasn’t exactly friendly to Christians.